Characteristics of alternative forms of state care for orphan children and children deprived of parental care - A. R. Zablotskiy (Kazimierz Wielki University, 2020)
Problem statement and purpose. Modern domestic society is characterized by a number of negative phenomena -impoverishment, unemployment, rising crime, mass labor migration both abroad and internally, related to the occupation of Crimea and hostilities in eastern Ukraine. All of them, directly or indirectly, cause disruption of the structure and functioning of the family, which, in turn, leads to an increase in the number of people such as orphans and children deprived of parental care. The system of social assistance and protection of this category of children combines both traditional and alternative forms of state care. Unfortunately, the reform of this system is too slow due to various reasons of social and economic, social and political and psychological and pedagogical nature. It is also worth noting that nowadays only the scientific basis for its functioning is being formed.Thus, Bader S., Bevz H., Vodyana O., Borysova V., Volynets L., Kobzar B., Komarova N., Ivanova I., Petrochko J., Kalibaba O., Makiychuk T., Orzhekhovska V., Pesh I., Piren M., Polyanychko A., Trubavina I. Turchyn O., Fedorova N., Kharkhan G., Chervonyy Yu. and others,studied the technologies of creation and organization of life of adoption and foster families, as well as children's homes (as alternative forms of state care), various aspects of stay and upbringing of children in such families.The content of social and pedagogical work in protection institutions and families where children are under protection is reflected in the works of domestic scientists: Bezpalko O., Hykava G., Zavgorodna T., Evdakh K., Ivanova A., Kapska A., Kurlyak I., Maksymova N., Naumenko T., Oleksyuk N., Pesh I., Sydorenko O., Chenbay I., Yurchenko T., Yaskal L., Yashchenko N. and others.Despite the wide and multifaceted scientific interest in this problem, the peculiarities of the formation and operation of alternative forms of care still remain unresolved. That is why the purpose of our study is to characterize the features of the functioning of alternative forms of care for orphans and children deprived of parental care and to determine the possibilities of their development. Research methods: to achieve this goal we used a set of methods: theoretical (conceptual and comparative analysis of philosophical, sociological, psychological and pedagogical, scientific and methodological and reference encyclopedic literature, regulatory and program documentation on research topics to clarify the content of basic concepts and study of the state of development of the researched problem in theory and practice); empirical (content analysis, questionnaires, pedagogical observation, study and generalization of independent characteristics and pedagogical experience, survey). Results. Based on the analysis of the scientific literature, the essence of the concepts "adoption", "custodianship/ care", "foster family", "family-type orphanage", "family patronage", "small group home", "deinstitutionalization" and "alternative care"is specified. Alternative forms of state protection of children as a social phenomenon are characterized, the relevance of deinstitutionalization and transformation of services for children is substantiated.